2016
DOI: 10.1152/ajpendo.00600.2014
|View full text |Cite
|
Sign up to set email alerts
|

Impact of maternal undernutrition around the time of conception on factors regulating hepatic lipid metabolism and microRNAs in singleton and twin fetuses

Abstract: We have demonstrated that periconceptional undernutrition and preimplantation undernutrition each resulted in decreased hepatic fatty acid ␤-oxidation regulators, PGC-1␣ (P Ͻ 0.05), PDK2 (P Ͻ 0.01), and PDK4 (P Ͻ 0.01) mRNA expression in singleton and twin fetuses at 135-138 days gestation. In singletons, there was also lower hepatic PDK4 (P Ͻ 0.01), CPT-1 (P Ͻ 0.01), and PKC (P Ͻ 0.01) protein abundance in the PCUN and PIUN groups and a lower protein abundance of PDPK-1 (P Ͻ 0.05) in the PCUN group. Interesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Apart from the classical transcriptional regulators, microRNAs (miRs) have been shown to participate in almost every metabolic homeostasis process, including adipogenesis [ 1 , 2 ], lipogenesis [ 3 ], and glucose-stimulated insulin secretion [ 4 , 5 ], in order to exert influence on metabolic pathways which are involved in the pathogenesis of nonalcoholic fatty liver disease (NAFLD) and nonalcoholic steatohepatitis (NASH) [ 6 ]. Recent research has demonstrated that miRs are able to regulate the expression of key genes involved in lipid homeostasis, including miR-122, miR-33, miR-106, miR-758, miR-26, miR-370, miR-378, let-7, miR-27, miR-143, miR-34a, and miR-335 [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the classical transcriptional regulators, microRNAs (miRs) have been shown to participate in almost every metabolic homeostasis process, including adipogenesis [ 1 , 2 ], lipogenesis [ 3 ], and glucose-stimulated insulin secretion [ 4 , 5 ], in order to exert influence on metabolic pathways which are involved in the pathogenesis of nonalcoholic fatty liver disease (NAFLD) and nonalcoholic steatohepatitis (NASH) [ 6 ]. Recent research has demonstrated that miRs are able to regulate the expression of key genes involved in lipid homeostasis, including miR-122, miR-33, miR-106, miR-758, miR-26, miR-370, miR-378, let-7, miR-27, miR-143, miR-34a, and miR-335 [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al (2019) found that miR-369-3p regulates the proliferation and migration of EEC (endometrioid adenocarcinoma) cells, suggesting that miR-369-3p can also inhibit adipocyte differentiation by inhibiting the expression of ATG10 in human body. Lie et al (2016) showed that miR-369-3p targeted PDPK-1 (3-phosphoinositide-dependent protein kinase-1) in sheep, and expression levels were negatively correlated. PDPK-1 is the key gene to initiate autophagy (Hu et al, 2021), and the expression of PDPK-1 and PPARγ resulted in a synergistic effect (Yin et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…CDK4 indirectly inhibits oxidative metabolism by controlling E2F1 transcription factors in muscle and brown adipose tissue (BAT) (Blanchet et al, 2011) and also promotes insulin signalling pathways in mature adipocytes (Lagarrigue et al, 2016). In sheep, miR-369-3p targets the key gene PDPK-1 that activates autophagy, and its expression is negatively correlated (Lie et al, 2016;Hu et al, 2021). The miR-369-3p can also regulate and inhibit the autophagy-related gene ATG10 (Liu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that lipid metabolism might be more sensitive to malnutrition during intrauterine development of fetus 2426 . Here we speculated that hypertriglyceridemia observed in adult SGA rats exposed to maternal undernutrition during pregnancy might be a result of abnormal expression of AMPK-α1/SREBP-1c/ACC-1 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Our study observed that the adult SGA rats showed weak ability to handle a lipid load resulting in increased serum TG levels, coincident with Choi’s study 23 . It has been reported that lipid metabolism might be more sensitive to malnutrition during intrauterine development of fetus 24 26 . Here we speculated that hypertriglyceridemia observed in adult SGA rats exposed to maternal undernutrition during pregnancy might be a result of abnormal expression of AMPK-α1/SREBP-1c/ACC-1 pathway.…”
Section: Discussionmentioning
confidence: 99%